Spatial distribution and driving force analysis of urban heat island effect based on raster data: A case study of the Nanjing metropolitan area, China. (October 2019) - Min, Min; Lin, Chen; Duan, Xuejun; Jin, Zhifeng; Zhang, Luocheng
Highlights: The driving factors of UHI have the highest explanatory power at 300 m grid. LULC had a significant effect on LST. Both intensity and type of human activities can strongly influence the UHI. The POI data and urban functional area data can be useful data sources for driving mechanism of UHI effect. Abstract: Human activities do not only change the land use/land cover (LULC), but also release a large amount of anthropogenic heat through intensive activities above ground, which drives the formation of urban heat island (UHI). This study used the Nanjing metropolitan area as the research area and taken 2017 as the observation time and chosen land surface characteristic parameters, point of interest (POI) density and urban functional area data to quantify the driving mechanism of human activities at a grid scale. The results indicated as follows: i) The response relationships between the LST and its driving factors have a clear scale effect at the grid scale. The driving factors had the highest explanatory power at the 300 m grid; ii) LULC had a significant effect on LST, impervious layers and bare soil increased the LST, vegetation and water relieved it; iii) In different urban functional areas, the relationship between LST and POI density was piecewise. In addition to density, the types of human activities also have a significant impact on the UHI, in which industrial heat release has the most significant effect on the local temperature of the city, followed by daily heat production and transportation heat release.